Laboratory bioefficacy of nine commercial formulations of temephos against larvae of Aedes aegypti (L.), Aedes albopictus Skuse and Culex quinquefasciatus Say. - Chen, C.D.; Lee, H.L.; Chan, C.K.; Ang, C.L.; Azahari, A.H.; Lau, K.W.; Sofian-Azirun, Mohd (Malaysian Society of Parasitology and Tropical Medicine, 2009)
The bioefficacy of nine commercial formulations of temephos against Aedes aegypti, Aedes albopictus and Culex quinquefasciatus larvae were evaluated in the laboratory. WHO larval bioassay with operational dosage of temephos at 1 mg/L was performed. The larval mortality was recorded every 5 minutes until complete mortality was achieved. All formulations of temephos exhibited various toxicity level against Ae. aegypti, Ae. albopictus and Cx. quinquefasciatus. Generally, larvae of Cx. quinquefasciatus was susceptible to all formulations of temephos, followed by Ae. aegypti and Ae. albopictus.